The impact of new infrastructure development on urban total factor carbon productivity-empirical evidence based on Chinese cities - Liu, Yang; Wang, Yu; Yan, Bing; Zhang, Hengshuo (Frontiers in Environmental Science, 2024)
Digital technology plays a vital role in driving toward a zero-carbon future. This paper explores whether new infrastructure, serving as carriers for digital technology, contributes to carbon reduction and efficiency gains in cities. Drawing on panel data from 280 Chinese cities spanning 2011 to 2019, we establish a theoretical analytical framework to investigate how new infrastructure influences urban carbon performance through the perspectives of influence, threshold, and spatial spillover effects. The study reveals that new infrastructures development has a contributing effect on the total factor carbon productivity of cities, with consistent results across various testing methods.Additionally, the threshold effect test suggests that the dual threshold of regional energy consumption influences the enhancing effect of new infrastructure on total factor carbon productivity, exhibiting nonlinear characteristics. Furthermore, the spatial spillover effect test suggests that new infrastructure construction accelerates the local carbon emission performance, while having a positive spillover effect on neighboring cities. This study provides innovative ideas and experiences from China for the global realization of simultaneous promotion of digital economy development and energy conservation and emission reduction. the quality of economic transformation (Solow, 1957;Khanna and Sharma, 2021). Compared with traditional productivity, total factor carbon productivity (TFCP) serves as a link between economic development and carbon emissions. It has become an important metric for reconciling economic growth with changes in carbon emissions. TFCP is also gaining traction in academic research.Studies have demonstrated that the advances in green technology advances, renewable energy innovations, and the opening of high-speed railways can serve as TFCP engines (Du and Li, 2019;